2016
DOI: 10.1037/stl0000070
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening scientific reasoning skills in introductory psychology: Evidence from community college and liberal arts classrooms.

Abstract: This research represents an extension of our prior article, published in Teaching of Psychology (Stevens & Witkow, 2014), which detailed the development and evaluation of a single module for training scientific reasoning skills in introductory psychology.Here we report on the development of a larger set of 8 modules, along with evaluation data from a 4-year baccalaureate liberal arts college (N ϭ 195 students) and a 2-year community college (N ϭ 94 students). Each module required 30 -45 min of class time and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 19 publications
5
33
0
Order By: Relevance
“…Although author affiliations indicate who designed, conducted, and wrote the research, this information may not always coincide with where the research was conducted. For example, some authors have partnered with teaching faculty at different colleges, including community colleges, to evaluate materials in different instructional settings (e.g., Kenyon et al, 2016; C. Stevens et al, 2016; L.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although author affiliations indicate who designed, conducted, and wrote the research, this information may not always coincide with where the research was conducted. For example, some authors have partnered with teaching faculty at different colleges, including community colleges, to evaluate materials in different instructional settings (e.g., Kenyon et al, 2016; C. Stevens et al, 2016; L.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that class structure or student characteristics influence pedagogy, it is thus unknown whether faculty teaching in different institutions or class contexts can meaningfully apply curricular innovations in their own classroom. At least one study that presented data from both a community college and 4-year Baccalaureate setting suggests that the effects of an intervention may vary in specific ways across different institutional contexts (C. Stevens et al, 2016). This represents an important direction for the SoTL research-namely identifying not only "what works?"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When traditional laboratory experiences are not a reasonable option, embedding scientific reasoning, and critical thinking modules into introductory psychology courses can significantly improve the skills important for conducting publishable research. For example, Stevens et al (2016) found that students showed significant gains in scientific reasoning after experiencing carefully planned lectures and discussion modules designed to promote scientific reasoning and critical thinking. Such curricular enhancements, paired with experiential learning activities, promote faculty and student scholarship.…”
Section: Prioritizing Experiential Learningmentioning
confidence: 99%
“…Even at the introductory level, the APA (2011) argues that students should be introduced to psychology as a scientific discipline. Although the APA Guidelines identify the importance of developing scientific reasoning and there is a multitude of classroom activities available with that goal in mind, assessment of these activities to determine if they are effective is less common (Stevens et al, 2016).…”
mentioning
confidence: 99%